Routine Cerebrospinal Fluid (CSF) Parameters in Patients With Spinal Muscular Atrophy (SMA) Treated With Nusinersen - Wurster, Claudia D.; Koch, Jan C.; Cordts, Isabell; Dreyhaupt, Jens; Otto, Markus; Uzelac, Zeljko; Witzel, Simon; Winter, Benedikt; Kocak, Tugrul; Schocke, Michael; Weydt, Patrick; Wollinsky, Kurt; et al. (Frontiers in Neurology, 2019)
Background: Nusinersen is an antisense-oligonucleotide (ASO) approved for treatment of 5q spinal muscular atrophy (SMA). Since the drug cannot cross the blood-brain barrier, it must be administered into the cerebrospinal fluid (CSF) space repeatedly by lumbar puncture. However, little is known whether ASOs have an impact on CSF routine parameters that may yield information on CSF flow and/or intrathecal inflammation. The objective of this study was to examine CSF routine parameters in SMA patients treated with nusinersen. Methods: Routine CSF parameters (white cell count, total protein, CSF/serum quotients of albumin (Qalb), lactate and oligoclonal IgG bands (OCB)) of 60 SMA patients (type 1, 2 and 3, aged 7 to 60 years) were retrospectively analyzed. Results: White cells ranged from 0 to 4/uL in CSF; a singular case of pleocytosis (8/uL) was observed in a patient in parallel with a systemic infection. Total protein and Qalb showed a mild increase from baseline to the following lumbar punctures (except for total protein in CSF at the fourth injection of nusinersen). Lactate levels revealed a stable course. In one patient, positive OCB in CSF were transiently observed. The slight change in total CSF protein and Qalb may be caused by repeated lumbar puncture and/or intrathecal administration of the drug. Conclusion: Our data suggest that a regular examination of routine CSF parameters in patients in which intrathecal ASOs are administered is important to obtain information on possible side effects and to gain further insights into intrathecal processes.